Study of preoperative radiotherapy for sarcomas of the extremities with intensity- modulation, image-guidance and small safety-margins (PREMISS) - Roeper, Barbara; Heinrich, Christine; Kehl, Victoria; Rechl, Hans; Specht, Katja; Woertler, Klaus; Toepfer, Andreas; Molls, Michael; Kampfer, Severin; Von Eisenharth-Rothe, Ruediger; Combs, Stephanie E. (BMC Cancer, 2015)
Background: The aim of the trial is to demonstrate that with the use of modern IMRT/IGRT and reduction of safety margins postoperative wound complications can be reduced. Methods/Design: The trial is designed as a prospective, monocentric clinical phase II trial. The treatment is performed with helical IMRT on the Tomotherapy HiArt System© or with RapidArc© IMRT as available. All treatments are performed with 6 MV photons and daily online CT-based IGRT. A dose of 50 Gy in 2 Gy single fractions (5 fractions per week) is prescribed. Restaging including MRI of the primary tumor site as well as CT of the thorax/abdomen is planned 4 weeks after RT. PET-examinations or any other imaging can be performed as required clinically. In cases of R1 resection, brachytherapy is anticipated in the 2nd postoperative week. Brachytherapy catheters are implanted into the tumor bed depending on the size and location of the lesion. Surgery is planned 5-6 weeks after completion of neoadjuvant RT. All patients are seen for a first follow-up visit 2 weeks after wound healing is completed, thereafter every 3 months during the first 2 years. The endpoints of the study are evaluated in detail during the first (2 weeks) and second (3 months) follow-up. Functional outcome and QOL are documented prior to treatment and at year 1 and 2. Treatment response and efficacy will be scored according to the RECIST 1.1 criteria. A total patient number of 50 with an expected 20 % rate of wound complications were calculated for the study, which translates into a 95 % confidence interval of 10.0-33.7 % for wound complication rate in a binomial distribution. Discussion: The present study protocol prospectively evaluates the use of IMRT/IGRT for neoadjuvant RT in patients with soft tissue sarcomas of the extremity with the primary endpoint wound complications, which is the major concern with this treatment sequence. Besides complications rates, local control rates and survival rates, as well as QOL, functional outcome and treatment response parameters (imaging and pathology) are part of the protocol. The data of the present PREMISS study will enhance the current literature and support the hypothesis that neoadjuvant RT with IMRT/IGRT offers an excellent risk-benefit ratio in this patient population.
CRIS-Team Scopus Importer:2023-03-08